Frequent problems in language learning in the story «El primer cónsul inglés», by Ricardo Palma - Mascaró del Castillo, Melanie (2021)
In this academic paper we will look at common mistakes made by foreign language learners. For this, we will take as a basis «El primer cónsul inglés» from the work Tradiciones peruanas by Ricardo Palma (2007), because in this story there are some examples of these mistakes, such as «—¡Oh, no! Patriotas conocer mí mucho... Montoneras my friends... estar amigos» (párr. 20), phrase spoken by the main protagonist Tomás Rowcroft when trying to speak in Spanish.